(untitled) (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : A service standards needs to be monitored in its implementation, and the monitoring function can find quickly, so that a mechanism for resolving and setting up a mechanism for prevention can be developed. Study aims to explain the monitoring function of the head department on the aplication of minimum service standards in the department population and civil registration in north minahasa. Based on the results and discussion of this research concluded, has not done well seen in the four functions monitoring is compliance, auditing, accounting, and explanation. Needed public awareness for orderly population administration and leadership must be more active in monitoring the course of service and the seriousness of the goverment to create a strategy. This research uses qualitative research methods, descriptive. informant research by as much as 10 (ten) informant: 1 person head of Department, 1 Secretary, 1 head of the sub. the General section and the staffing, 5 civil State apparatus, 2 people community. data collection techniques used i.e., interview techniques, techniques of observation/observation, and technical documentation. data analysis techniques used, namely the reduction of data, data presentation, and conclusion. Key words : Monitoring Function, Minimum Service Standards